1991
DOI: 10.1302/0301-620x.73b3.1670448
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging of meniscal and cruciate injuries of the knee

Abstract: We investigated 133 knees with suspected meniscal or cruciate injuries by magnetic resonance imaging, and compared the findings with those at arthroscopy. MRI was found to be highly sensitive, specific and accurate in the evaluation of the menisci and the anterior cruciate ligament.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
32
2
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(40 citation statements)
references
References 10 publications
5
32
2
1
Order By: Relevance
“…Unfortunately, arthroscopies are invasive and require a skilled surgeon. MRI has become a popular and practical tool for the evaluation of ACL injuries with its high degree of accuracy and sensitivity as reported in the literature [4].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, arthroscopies are invasive and require a skilled surgeon. MRI has become a popular and practical tool for the evaluation of ACL injuries with its high degree of accuracy and sensitivity as reported in the literature [4].…”
Section: Discussionmentioning
confidence: 99%
“…Whilst some authors have reported excellent sensitivity and specificity, others have reported less favourable results [6,7]. Acknowledging this variability in outcomes, the objective of this study was to determine the diagnostic accuracy of complete ACL rupture using MRI by comparing imaging results to the gold standard arthroscopic findings.…”
Section: Introductionmentioning
confidence: 99%
“…Ruwe et al [12] reported that preoperative MRI can prevent unnecessary Arthroscopy in 50% of patients, so is of great value and must be done preoperatively. Boeree et al [13] believe that clinical examination is of minor significance with sensitivity in diagnosing medial meniscus, lateral meniscus and ACL tear of 67%, 48% and 55% respectively.…”
Section: Discussionmentioning
confidence: 99%